The Impact of School Voucher Program on School Dropouts in Indonesia - Hery Arif Listiyanto; Riatu Mariatul Qibthiyyah (Universitas Negeri Malang, 2022)
The Indonesian government implemented a school voucher program called Program Indonesia Pintar (PIP) to prevent students from dropping out. PIP is a development of Bantuan Siswa Miskin (BSM). This study empirically analyzes the impact of PIP in reducing the possibility of dropping out at every level of education. The estimation method used in this research is Probit Regression and Marginal Effect. This study compares BSM and PIP's effectiveness and includes PKH (Program Keluarga Harapan) as one of the control variables. The estimation results show that the PIP policy is more effective than BSM in reducing the possibility of dropping out of school at every level of education, both for the full sample and for the subsample of students from families with expenditure levels below the poverty line. PIP has a more significant effect on the subsample of students from poor families than the full sample. Students from poor families who received PIP were 1.9 percent less likely to drop out of school for elementary school. Meanwhile, at the junior high school level, it was 5.1 percent, and at the senior high school level, it was 2.8 percent. In general, there is no impact of PKH in reducing school dropouts.Keywords: Education, PIP, school dropouts, marginal effect